Aquatic fauna from the Takarkori rock shelter reveals the Holocene central Saharan climate and palaeohydrography - Van Neer, Wim; Alhaique, Francesca; Wouters, Wim; Dierickx, Katrien; Gala, Monica; Goffette, Quentin; Mariani, Guido S.; Zerboni, Andrea; di Lernia, Savino (PLOS ONE, 2020)
The abundant faunal remains from the Takarkori rock shelter in the Tadrart Acacus region of southwestern Libya are described. The material that covers the period between 10,200 to 4650 years cal BP illustrates the more humid environmental conditions in the Central Sahara during early and middle Holocene times. Particular attention is focussed on the aquatic fauna that shows marked diachronic changes related to increasing aridification. This is reflected in the decreasing amount of fish remains compared to mammals and, within the fish fauna, by changes through time in the proportion of the species and by a reduction of fish size. The aquatic fauna can, in addition, be used to formulate hypotheses about the former palaeohydrographical network. This is done by considering the possible location of pre-Holocene relic populations combined with observations on the topography and palaeohydrological settings of the Central Sahara.